PENGARUH JUMLAH TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN BERAU - Endah Susanti (ECO-BUILD, 2025)
The purpose of this study is to investigate and describe the influence of the number of workers on economic growth in Berau Regency. The sample used in this study consists of data on the number of workers from 2017 to 2022. The analysis tool employed is Statistical Package for the Social Sciences (SPSS) version 25.0, using a Simple Linear Regression test.The results of this study indicate that the number of workers has a significant partial effect on economic growth in Berau Regency. This is evidenced by the results of the t-test, where the calculated t-value exceeds the t-table value (2.236 > 2.048), and the significance value (Sig) is less than 0.10. These findings demonstrate that the number of workers significantly influences economic growth in Berau Regency.